2007
DOI: 10.1001/archderm.143.2.203
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical, Histologic, and Molecular Study of 9 Cases of Congenital Dermatofibrosarcoma Protuberans

Abstract: Background:The diagnosis of dermatofibrosarcoma protuberans (DFSP) in childhood is often difficult because of the deceptive appearance of the lesions. Little is known about congenital DFSP, the frequency of which is probably underestimated because the initial lesion may pass unnoticed.Observations: We studied 9 DFSP congenital cases (8 plaques and 1 nodule) initially suspected to be benign lesions. The first biopsies or excisions were performed after a delay of 5½ months to 15 years. All cases were CD34ϩ. Hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 37 publications
(53 reference statements)
7
70
1
2
Order By: Relevance
“…Other authors have reported similar findings, and the average age at diagnosis of congenital DFSP has been found to be 14 years (4,16). Possible explanations could be a delay in initial presentation to the doctor by patients' parents because of the apparently harmless nature of the primary lesion; lack of clinical suspicion by the pediatrician or dermatologist due to confusion of the tumor with more common, benign lesions that occur in this age group; or incorrect initial histologic diagnosis, especially before immunohistochemical analysis with the CD34 marker was available (15,23,24). DFSP most commonly occurs between the ages of 30 and 50 years (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported similar findings, and the average age at diagnosis of congenital DFSP has been found to be 14 years (4,16). Possible explanations could be a delay in initial presentation to the doctor by patients' parents because of the apparently harmless nature of the primary lesion; lack of clinical suspicion by the pediatrician or dermatologist due to confusion of the tumor with more common, benign lesions that occur in this age group; or incorrect initial histologic diagnosis, especially before immunohistochemical analysis with the CD34 marker was available (15,23,24). DFSP most commonly occurs between the ages of 30 and 50 years (25).…”
Section: Discussionmentioning
confidence: 99%
“…DFSP is characterized in 70% to 90% of cases by specific cytogenetic features, such as the reciprocal translocation t(17;22) (q22;q13), which results in fusion of the COL1A1 gene at chromosome 17q21.3 with the second exon of the PDGFB gene at chromosome 22q13.1 (30,37). In children, this has been described as a balanced or an unbalanced translocation, but with the absence of ring chromosomes (15,16,22,32). This translocation may be detected in patient tumor samples using conventional cytogenetic analyses, PCR, or FISH.…”
Section: Discussionmentioning
confidence: 99%
“…The artificial bacterial chromosome clones RP11-93L18, RP11-89F2, RP11-959K5, and RP11-642F17 were used as probes to detect the COL1A1-PDGFB fusion gene as previously described (8,9). FISH analysis was done on metaphase cell preparations for 1 sample, on interphase cell suspensions for 14 samples, and on formalin-fixed and paraffin-embedded tissue sections for 25 samples (10).…”
Section: Conventional and Molecular Cytogenetic Analysismentioning
confidence: 99%
“…In our previous experience (Llombart et al, accepted for publication), we observed that 76% is detected using RT-PCR in paraffin embedded tissue samples. FISH has been performed using both PDGFB break-apart and COL1A1/PDGFB dual color dual fusion (DCDF) non-commercial probe strategies (Abbott et al, 2006;Craver et al, 2006;Maire et al, 2007;Macarenco et al, 2008;Patel et al, 2008;Segura et al, 2011). It has been postulated that dual fusion probes are better than break-apart regarding sensitivity because their false positive rate in normal tissues is very low (Ventura et al, 2006).…”
Section: Introductionmentioning
confidence: 99%